Viking silver, hoards and containers : the archaeological and historical context of Viking-age silver coin deposits in the Baltic c. 800-1050 /: the archaeological and historical context of Viking-age silver coin deposits in the Baltic c. 800-1050. (2019) - Gruszczynski, Jacek, 1980-
No abstract available